Analisis Benchmarking Terhadap Kinerja Perusahaan Kontraktor Di Dinas Pupr Kota Blitar - Dessy Kusuma Wardani; Edy Swasono (REVITALISASI : Jurnal Ilmu Manajemen, 2020)
This study aims to identify the dominant factors of the successful implementation of benchmarking on the performance of contracting companies and test the significance of the application of benchmarking on the performance of contracting companies. The research sample was saturated samples of 65 qualified contractor companies. The method and type of research used were correlational methods of multiple regression analysis using SPPS. The results of the study concluded that 1.Benchmarking significantly influences the performance of contracting companies in the Blitar City DPUPR; 1. The ranking of success factors for the Blitar City contractor companies in the process of implementing benchmarking (1) planning, (2) data collection, (3) acception and action and (4) analysis; 2.Benchmarking has proven to significantly improve company performance as measured by increasing (1) Corporate Finance (2) Company productivity, (3) DPUPR Consumer Satisfaction, (4) Community Satisfaction, (5) Quality of the company's construction technical personnel, (6) Satisfaction employee work, (7) Project acquisition rate in one year, (8) Effective completion of construction work, (9) Construction product quality.